Thermo-Mechanics Applications and Engineering Technology (Springer International Publishing, 2018)
This book focuses on the dissemination of information of permanent interest in thermo-mechanics applications and engineering technology. Contributions have clear relevance to industrial device and a relatively straightforward or feasible path to application. Chapters are sought that have long-term relevance to specific applications including convective heat transfer, fluid mechanics, combustion, aerodynamics, hydrodynamics, turbomachinery and multi-phase flows. In fact, many aspects in industrial operations and daily life are closely related to thermo-mechanics processes. Along with the development of computer industry and the advancement of numerical methods, solid foundation in both hardware and software has been established to study the processes by using numerical simulation methods, which play important roles in the ways of extending research topics, reducing research costs, discovering new phenomena, and developing new technologies. The presented case studies and development approaches aim to provide the readers, such as engineers and PhD students, with basic and applied studies broadly related to the Thermo-Mechanics Applications and Engineering Technology.